PENGARUH MODEL PEMBELAJARAN COPY THE MASTER TERHADAP KEMAMPUAN MENULIS CERPEN SISWA KELAS IX SMP NEGERI 2 NA IX-X TAHUN AJAR 2022/2023 - Indah Aprilia; Inayah Hanum (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This research was conducted to find out how well the ability to write short stories of class IX students of SMPN 2 NA IX-X before and after implementing the Copy The Master learning pattern. In addition, it also aims to find out how the Copy The Master learning pattern affects the ability to write short stories for class IX SMPN 2 NA IX-X for the 2022/2023 academic year. Students who took part in this study were 64 people. 32 students from class IX-1 were used as samples. One-Group Pre-test Post-test Design was used in this study. The ability to write short stories for class IX students of SMPN 2 NA IX-X before using the Copy The Master learning model according to the pre-test results was sufficient with an average score of 62.12; 11.12 standard deviation; 1.99 standard error. Regarding the results of the posttest, class IX students of SMPN 2 NA IX-X were able to write short stories for the 22/2023 school year with an average score of 76.43 which is considered good; standard deviation 7.69; standard error = 1.38. The tcount value tested is 5.91; ttable of 1.69, this proves that the research hypothesis or Ha is accepted because tcount (5.91) > ttable (1.69). The ability to write short stories for class IX students of SMPN 2 NA IX-X for the 2022/23 academic year is strongly influenced by the Copy The Master learning pattern. Keywords: Influence, Copy The Master, short story.